Moderate monism, persistence and sortal concepts - Noonan, Harold (2007)
Coincidence (e.g., of a statue and the piece of bronze which constitutes it) comes in two varieties – permanent and temporary. Moderate monism (about coincidence) is the position that permanent coincidence, but not temporary coincidence, entails identity. Extreme monism (also known as the stage theory) is the position that even temporary coincidence entails identity. Pluralists are opponents of monism tout court. The intuitively obvious, commonsensical position (= my own position) is moderate monism. It is therefore important to see if it can be sustained.